2015
DOI: 10.1016/j.exger.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic lineage skewing and intestinal epithelia degeneration in aged mice with telomerase RNA component deletion

Abstract: A deletion of telomerase RNA component (Terc−/−) in C57BL/6 (B6) mice resulted in hematopoietic lineage skewing with increased neutrophils and CD11b+ myeloid cells and decreased red blood cells and CD45R+ B lymphocytes when animals reach ages older than 12 months. There was no decline in bone marrow (BM) c-Kit+Sca-1+Lin− (KSL) cells in old Terc−/− mice, and the lineage skewing phenomenon was not transferred when BM cells from old Terc−/− donors were transplanted into young B6 recipients. Necropsy and histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
(51 reference statements)
0
5
1
Order By: Relevance
“…A link between intestinal infection and inflammation with impaired telomerase activity has also been shown in these animals. In contrast to our findings in vitro , normalization of myeloid cell numbers in TERC -/- mice following antibiotic treatment had no effect on the HSC compartment, suggesting that the effect of loss of TERC on myelopoietic changes is indirect ( Chen et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A link between intestinal infection and inflammation with impaired telomerase activity has also been shown in these animals. In contrast to our findings in vitro , normalization of myeloid cell numbers in TERC -/- mice following antibiotic treatment had no effect on the HSC compartment, suggesting that the effect of loss of TERC on myelopoietic changes is indirect ( Chen et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Telomere complex impairment is one of the first explanations for bone-marrow failure in dyskeratosis congenita, but several groups have highlighted a possible role for bone marrow mesenchymal stem cells in disease pathology. Specifically, mesenchymal stem cells lacking TERC are unable to sufficiently support healthy hematopoiesis ( Balakumaran et al, 2015 ; Chen et al, 2015 ). Nevertheless the role of specific members of the telomerase complex in telomeropathy progression remains inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that telomere shortening in the intestine predisposes to inflammation through pathways that are incompletely understood and mainly attributed to ISC compromise 33,45,46 . To determine the impact of telomere dysfunction on the intestinal epithelium (IE), we performed RNA-seq analysis on the IE from the proximal intestine of young WT and TKO mice.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of immature enterocytes explains the observed barrier defect in mice and, potentially, in human patients with intestinal inflammation, in which a barrier defect has been suggested to drive intestinal inflammation 36,45,66 . This barrier defect predisposes to inflammation through a pathological interaction with the microbiome based on the significant amelioration of inflammation when the microbial load is reduced after a fructose-rich diet or in aged TKO mice 45,46 . The importance of the intestinal epithelium as a driver of intestinal inflammation is further strengthened by the finding that intestinal inflammation is reduced when telomerase is reactivated specifically in the intestinal epithelium 45 .…”
Section: Discussionmentioning
confidence: 99%